PENERAPAN SISTEM PERSAMAAN LINEAR DALAM EKONOMI: Application of Systems of Linear Equations in Economics - Piranda, Koni; Fitradinata, Kheqal; Nugraha, Riyandi Fatur; Zakiah, Nina (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2024)
The field of mathematics is a scientific discipline that can solve economic problems. This is because the field of mathematics can be used in dealing with financial audit problems that use images and numerical ideas in critical thinking. Apart from that, branches of mathematics such as the application of systems of linear equations can influence economics. Therefore, this research is intended to find out in more depth about the Application of Systems of Linear Equations in Economics. The aim of this research is to find the effect of implementing systems of linear equations in economics. To achieve this goal, the author uses library research methods with the aim of collecting data or information with the help of technology in the form of computers and various sources in libraries such as books, journals, articles and similar research results. From this research, several explanations regarding the Application of Systems of Linear Equations which can influence the field of Economics are produced, including: 1). The application of the Linear Equation system can influence Demand in the economic sector; 2). The application of the Linear Equation system can influence supply in the economic sector; 3). Application of a Linear Equation System can result in market balance (market equilibrium); 4). Implementation of a Linear Equation System can affect Tax; 5). Application of the Linear Equation System can affect subsidies. From the research conducted, the author hopes that it will become a reference in the world of economics and become a reference in carrying out efforts to improve the economy.